2018
DOI: 10.1177/2332858418815661
|View full text |Cite
|
Sign up to set email alerts
|

School Climate, Student Engagement, and Academic Achievement: A Latent Variable, Multilevel Multi-Informant Examination

Abstract: This study tested the authoritative school climate theory that schools characterized by high structure and student support have greater levels of student engagement and that these factors are associated with higher academic achievement, as indicated by school graduation rates and school performance on state-mandated testing. The model was tested through a multilevel multi-informant structural model on a statewide sample of 60,441 students and 11,442 teachers in 298 high schools. Consistent with the authoritati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(103 citation statements)
references
References 77 publications
4
90
1
8
Order By: Relevance
“…Second, our findings show that in both the United States and Korea, TSMC positively mediates the relationship between PDME and the perceptions of school climate. In other words, the benefits of participating in PDME go beyond TSMC to enhance school climate, which has been shown to have positive effects on students’ behavioral, social, and academic outcomes (Booth & Gerard, 2014; Konold et al, 2018; Lewis et al, 2017). This aligns with Judith Warren Little’s (1993) argument where she stated, “The most promising of these efforts [professional development] engage teachers collectively in studying classroom practices in ways that sometimes lead to more systemic changes at the school level” (p. 131).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, our findings show that in both the United States and Korea, TSMC positively mediates the relationship between PDME and the perceptions of school climate. In other words, the benefits of participating in PDME go beyond TSMC to enhance school climate, which has been shown to have positive effects on students’ behavioral, social, and academic outcomes (Booth & Gerard, 2014; Konold et al, 2018; Lewis et al, 2017). This aligns with Judith Warren Little’s (1993) argument where she stated, “The most promising of these efforts [professional development] engage teachers collectively in studying classroom practices in ways that sometimes lead to more systemic changes at the school level” (p. 131).…”
Section: Discussionmentioning
confidence: 99%
“…The positive impacts of school climate have been well documented. For instance, research found that school climate had a positive impact on academic engagement and achievement (Konold et al, 2018), self-esteem (Booth & Gerard, 2014), and emotional health (Lewis et al, 2017). Research also showed that teachers' perceptions of school climate were positively associated with reducing disruptive behavior (Mitchell et al, 2010) and improving academic achievement (Bear et al, 2014;B.…”
Section: Pdme Tsmc and School Climatementioning
confidence: 99%
“…Feeling good about learning and having a sense of belonging would trigger students' passion for learning, which is the foundation of intrinsic motivation and trigger engagement (Furlong et al, 2003;Libbey, 2004). Likewise, creating an authoritative school climate with high structure and student support can nurture student engagement (Konold et al, 2018). This could be applicable in Vietnamese high-school context, because students there are often strictly monitored by their teachers and supervisors, but there has been a lack of student support service, especially in terms of self-learning skills.…”
Section: Discussionmentioning
confidence: 99%
“…Several programs aimed at improving school climate have been developed to promote the quality of scholastic life (O’Brennan and Bradshaw, 2013). In fact, there is evidence that students are more engaged in school and attain higher academic achievement in schools with a positive school climate (Wang and Degol, 2016; Konold et al, 2018). School climate can be studied at the group level, by aggregating the data collection of the different actors (students, teachers, managers, parents) involved in the school context (Cornell et al, 2016).…”
Section: Introductionmentioning
confidence: 99%